Literatura słowacka w Polsce w latach 2007—2013 - Buczek, Marta (Przekłady Literatur Słowiańskich, 2014)
Slovak literature in Poland in years 2007—2013 The author of the article describes in detail the Slovak literature which was translated in Poland in the years 2007—2013. In her article she also deals with contemporary Polish publishers market which publishes translations of „small”, „peripheral” literatures. She analyzes translation literature with view of its entry into a new literary context. Key words: Slovak literature in translation, Slovak literature in Poland, literary translation.